The coccid-tending ant genus Acropyga Roger (Hymenoptera: Formicidae) and its obligate associated myrmecophilous scale insect genus Eumyrmococcus Silvestri (Hemiptera: Xenococcidae) new to Italy - Scupola, Antonio; Durante, Antonio; Giannuzzi, Francesco; Pellizzari, Giuseppina (Fragmenta entomologica, 2022)
The ant genus Acropyga Roger, 1862 (Hymenoptera: Formicidae) and its associated myrmecophilous scale insect genus Eumyrmococcus Silvestri, 1926 (Hemiptera: Xenococcidae) are reported from Italy for the first time. These records are based on some alates of Acropyga paleartica Menozzi, 1936 with females of Eumyrmococcus corinthiacus Williams, 1993 carried in their mandibles, collected in Salento area (Apulia region, South Eastern Italy) in 2020.